Nesting of Rare Vultures in Katerniaghat Wildlife Sanctuary, Uttar Pradesh, India - Sethi, Janmejay; Chuahan, N. P. S. (Indian Forester, 2010)
Out of the 9 species of vultures, more than 90 per cent of two species of vultures, the white-rumped and long-billed, have been wiped out. The main reason for such decline in the population has been attributed to presence of diclofenac. The manufacture of diclofenac for cattle is now banned. But it is still used as people have stocks and they are unwilling to throw away. But there is an acceptable "vulture-safe" alternative available i.e. meloxicam.Though several breeding centres have been set up to restock the vulture population, occurrence of natural nesting sites are quite rare. The authors critically observed the movement of vultures. End of winter (October-March) is the nesting season of Gyps vultures and an area of c. 2 km2 of Semal and Haldu plantation was identified as the roosting place. Two species of vultures (white-rumped and king vultures) were found nesting in the sal and teak dominated mixed forest and scrub forest with grasslands. Maximum numbers of nests (65.4%) were seen on the semal (Bombax ceiba). A total of 39 nests (built on 26 trees ) occupied by white-rumped and king vultures were counted in Sadar beat of Katrniaghat range during April, May and June. Most of the trees had just one nest.